2006
DOI: 10.1186/1471-230x-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary syndrome in patients with chronic liver disease: role of pulse oximetry

Abstract: Background: Hepatopulmonary syndrome (HPS) is a rare complication of liver diseases of different etiologies and may indicate a poor prognosis. Therefore, a simple non-invasive screening method to detect HPS would be highly desirable. In this study pulse oximetry was evaluated to identify patients with HPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
7
29
0
4
Order By: Relevance
“…HPS has been reported in 10-30% of patients referred for LTx evaluation [60,61], but in only 1% of patients with chronic liver disease in the non-transplant setting [62]. The presence of either intrapulmonary shunts or oxygenation abnormalities are more common, occurring in 25-65% of patients awaiting LTx and in 5% of patients in the non-transplant setting [61][62][63][64]. HPS is usually diagnosed during the sixth decade of life and there is no specific association with sex or aetiology of liver disease.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…HPS has been reported in 10-30% of patients referred for LTx evaluation [60,61], but in only 1% of patients with chronic liver disease in the non-transplant setting [62]. The presence of either intrapulmonary shunts or oxygenation abnormalities are more common, occurring in 25-65% of patients awaiting LTx and in 5% of patients in the non-transplant setting [61][62][63][64]. HPS is usually diagnosed during the sixth decade of life and there is no specific association with sex or aetiology of liver disease.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…This suggests that the use of exercise SaO 2 testing is helpful in early identification of HPS and also that screening for hypoxemia in BA patients after the Kasai operation using a noninvasive technique such as pulse oximetry might confirm the early diagnosis of HPS. Deibert et al, in a prospective study of adult patients with liver cirrhosis, showed the significance of SaO 2 screening and its correlation with the shunt ratio; they also suggested the usefulness of pulse oximetry [6].…”
Section: Discussionmentioning
confidence: 98%
“…There are extensive data supporting the utility of pulse oximetry in various clinical settings, and serial pulse oximetry has been used in chronic pulmonary disorders such as COPD, sleep apnea and patients with a tracheostomy on long-term mechanical ventilation [5-8, 16, 17]. A single measurement of SpO 2 with pulse oximetry accurately detects hypoxemia and has been established as a useful screening tool for HPS [2,18,19]. However, serial measurements of SpO 2 have not been evaluated to assess progression or development of HPS prior to our study.…”
Section: Discussionmentioning
confidence: 99%